Conserving diversity in Irish plant–pollinator networks - Laura Russo; Úna Fitzpatrick; Michelle Larkin; Sarah Mullen; Eileen Power; Dara Stanley; Cian White; Aoife O'Rourke; Jane C. Stout (Ecology and Evolution, 2022)
Abstract Beneficial insects provide valuable services upon which we rely, including pollination. Pollinator conservation is a global priority, and a significant concern in Ireland, where over half of extant bee species have declined significantly in recent decades. As flower‐visiting insects rely on flowering plants, one way to conserve and promote pollinator populations is to protect high‐quality habitat. We analyzed the structure of insect–flower interactions from multiple habitat categories in a large database of interactions from Ireland. Our primary goals were to compare spatial and temporal variation in Irish network structures, compare Irish networks to published networks from other countries, and provide evidence‐based recommendations for pollinator conservation in Ireland by identifying well‐visited plant species that may promote high pollinator diversity, abundance, and functional complementarity. Habitat types within Ireland differed substantially: seminatural grasslands had the highest pollinator species richness and largest number of unique pollinator species, while intensively managed habitats exhibited negative asymmetry (more plant than pollinator species). This negative asymmetry is notable because most plant–pollinator networks exhibit a positive asymmetry. Within intensively managed habitats, agricultural and urban habitats differed. Urban habitats had the highest number of non‐native plant species while agricultural habitats had the lowest pollinator species richness. We also found Irish networks varied across the growing season, where July had the highest plant and insect species richness. When comparing Irish networks to published networks from other countries, we found Irish networks had a higher ratio of plant species to pollinator species, and that this difference was most evident in agricultural habitats. This ratio means the typical network asymmetry (more pollinator than plant species) was flipped (more plant than pollinator species) in the Irish network. We conclude that conserving seminatural grasslands in Ireland will be an essential component of pollinator conservation and identify thirty‐five plant species important for restoring seminatural habitats.